Development of a Motorcycle Charging System Trainer as a Student-Centered Learning Medium for Vocational Automotive Education - Teofilus Isandri; Muhammad Amiruddin; Ginanjar Budiarsyah (Jurnal E-Komtek, 2026)
The Indonesian government prioritizes vocational education as a human resource development strategy to meet industrial needs. This study developed a Trainer for the Motorcycle Charging System at the PVTO Laboratory of PGRI University Yogyakarta using the ADDIE model. The Design phase utilized Autodesk Fusion 360 to design an ergonomic hollow steel frame, while the Development phase included frame fabrication, installation of a standard wiring system, and integration of digital measuring instruments for real-time visualization of electrical parameters. Technical testing results showed 100% system functionality and very high physical feasibility with a validation score of 4.71/5.00. This product has proven effective as a troubleshooting tool that facilitates systematic diagnosis and supports students’ mastery of mechanical competencies.